2021
DOI: 10.24953/turkjped.2021.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Can early hyperglycemia affect the morbidity/mortality of very low birth weight premature infants?

Abstract: Background. The study aimed to examine the effect of early hyperglycemia on the morbidity/mortality of very low birth weight premature infants. Methods. This retrospective study included all premature infants with gestational age ≤32 gestational weeks, hospitalized at the Department of Intensive Neonatal Care, Clinical Center Kragujevac, during the period 2017-2019. Hyperglycemia was defined as glycemia of ≥12 mmol/l in one measurement, or > 10 mmol/l in two measurements, at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Hyperglycemia is one of the most common metabolic conditions in extremely low birth weight infants (ELBW). It has been associated with significant morbidity and mortality, including intraventricular hemorrhage, retinopathy of prematurity, necrotizing enterocolitis, and abnormal neurologic examination at two years of age [5][6][7][8]. Several risk factors contribute to the development of hyperglycemia in preterm infants, including gestational age, low birth weight, stress, excessive glucose administration, parenteral nutrition, and the administration of some drugs, such as corticosteroids, phenytoin, or theophylline [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia is one of the most common metabolic conditions in extremely low birth weight infants (ELBW). It has been associated with significant morbidity and mortality, including intraventricular hemorrhage, retinopathy of prematurity, necrotizing enterocolitis, and abnormal neurologic examination at two years of age [5][6][7][8]. Several risk factors contribute to the development of hyperglycemia in preterm infants, including gestational age, low birth weight, stress, excessive glucose administration, parenteral nutrition, and the administration of some drugs, such as corticosteroids, phenytoin, or theophylline [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Two prospective studies found that hyperglycemia is associated with intracranial hemorrhage. [23,24]. High blood glucose concentrations increase the risk of early death and grade 3 or 4 intraventricular bleeding [25].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that mechanical ventilation increases the chance of developing hyperglycemia three times(P = 0.032) [4]. A study showed that hyperglycemia was signi cantly associated with a shorter duration of mechanical ventilation (P = 0.006) [24]. This may be related to stress hyperglycemia in premature infants induced by mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatology is one area where automated microfluidic devices may be particularly effective. Preterm newborns may have as little as 50 mL of total blood volume and are at an elevated risk for a number of health conditions including hypoglycemia [ 6 ], infections [ 7 ] and jaundice [ 8 , 9 ]. To improve health outcomes, preterm infants must be carefully monitored and screened for these conditions by measuring biomarkers in the blood.…”
Section: Introductionmentioning
confidence: 99%